A rapid in situ electrochemical transformation of the biphase Zn3(OH)2V2O7·2H2O/NH4V4O10 composite for high capacity and long cycling life aqueous rechargeable zinc ion batteries. Issue 6 (21st January 2022) - Gu, Yuanxiang; Zhang, Lu; Li, Di; Sheng, Rui; Li, Feng; Wang, Lei
Abstract : The Zn3 (OH)2 V2 O7 ·2H2 O/NH4 V4 O10 nanobelts transform into Zn3 V2 O7 (OH)2 -based materials by an in situ electrochemical conversion, which act as an active cathode for high capacity aqueous zinc ion batteries. Abstract : 2D Zn3 (OH)2 V2 O7 ·2H2 O/NH4 V4 O10 nanobelts are synthesized by a simple hydrothermal route. This is the first report on the transformation of Zn3 (OH)2 V2 O7 ·2H2 O/NH4 V4 O10 (ZnVO/NVO) nanobelts into Zn3 (OH)2 V2 O7 ·2H2 O-based materials by an in situ electrochemical conversion, which act as an active cathode for high capacity and long cycling life aqueous rechargeable zinc ion batteries. By tuning the hydrothermal reaction time, the ZnVO and NVO content in the ZnVO/NVO can be controlled. The ZnVO/NVO nanobelts with a ZnVO content of 24.1% exhibit superior electrochemical performance with a maximum discharge capacity of 337 mA h g −1 at a current density of 0.5 A g −1 . At a high current density of 10.0 A g −1, the ZnVO/NVO cathode still exhibits a maximum discharge capacity of 187 mA h g −1, and keeps a reversible capacity of 176 mA h g −1 with a maximum capacity retention of 94% after 2000 cycles. The synergistic effect of intercalated Zn 2+ and NH4 + ions as well as structural water provides the cathode materials with excellent electrochemical performance.